Is there a Role for Funding in Explaining Recent U.S. Banks' Failures? - Bologna, Pierluigi (IMF Working Papers; Working Paper ;, 2011)
This paper tests the role of different banks' liquidity funding structures in explaining the banks' failures, which occurred in the United States between 2007 and 2009. The results highlight that funding is indeed a significant factor in explaining banks' probability of default. By confirming the role of funding as the driver of banking crisis, the paper also recognizes that the new liquidity framework proposed by the Basel Committee on Banking Supervision appears to have the features to strenghten banks' liquidity conditions and improve financial stability. Its correct implementation together with closer supervision of banks' liquidity and funding conditions appear, however, the determinant for such improvements to be achieved.